Un Giurista Dimenticato - Ruggiero, Gianluca (Revista Amagis Jurídica, 2024)
A forgotten jurist: Raul Alberto Frosali The paper intends to reconstruct the thought and work of Raul Alberto Frosali, through an analysis of the writings of this important Florentine author, adherent to the Positive School, also in relations with fascist ideology, up to the examination of the “legacy” cultural and scientific that he left to posterity.